2014
DOI: 10.1051/0004-6361/201423833
|View full text |Cite
|
Sign up to set email alerts
|

The 2.35 year itch of Cygnus OB2 #9

Abstract: Context. The wind-wind collision in a massive star binary system leads to the generation of high temperature shocks that emit at X-ray wavelengths and, if particle acceleration is effective, may exhibit non-thermal radio emission. Cyg OB2#9 is one of a small number of massive star binary systems in this class. Aims. X-ray and radio data recently acquired as part of a project to study Cyg OB2#9 are used to constrain physical models of the binary system, providing in-depth knowledge about the wind-wind collision… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 77 publications
2
26
0
Order By: Relevance
“…5 of Stevens & Pollock 1994). In their 3D hydrodynamical simulations of Cyg OB2 #9, Parkin et al (2014) reported a drop of the pre-shock wind velocity by 18% at periastron. 9 Sgr and Cyg OB #9 have very similar eccentricities, but the orbital separation of 9 Sgr is twice as wide, and its components are slightly less luminous than those of Cyg OB2 #9.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…5 of Stevens & Pollock 1994). In their 3D hydrodynamical simulations of Cyg OB2 #9, Parkin et al (2014) reported a drop of the pre-shock wind velocity by 18% at periastron. 9 Sgr and Cyg OB #9 have very similar eccentricities, but the orbital separation of 9 Sgr is twice as wide, and its components are slightly less luminous than those of Cyg OB2 #9.…”
Section: Discussionmentioning
confidence: 93%
“…Both effects should reduce the importance of radiative inhibition in 9 Sgr compared to Cyg OB2 #9. A detailed assessment of the importance of radiative inhibition requires 3D hydrodynamic simulations as performed by Parkin et al (2014), which is beyond the scope of the present work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work, the magnetic field strength scales with ζ 1/2 B and V rot . The assumptions on the field configuration and slow rotation used by Parkin et al (2014) are probably generally not adapted to PACWB. In particular, if the field is strong, the impact of the magnetic field on the wind, for example, magnetic wind confinement, should be taken into account (ud-Doula & Owocki 2002;ud-Doula et al 2008), and massive stars are often rapid rotators (e.g.…”
Section: Upper Limit On Undetected Fieldsmentioning
confidence: 99%
“…Extrapolating this to the surface of the stars with typical distances between the stagnation point and the photosphere, we obtain values of the stellar magnetic field strength between one G and a few thousand G, depending on the system and on the assumptions (e.g. Parkin et al 2014). Magnetic fields detected in single massive stars have a polar field strength between one hundred and several thousand G (see e.g.…”
Section: Introductionmentioning
confidence: 99%